Influence of Taxation System on Usage of Enterprise Production Resources - L. V. Hryntsevich; I. M. Babuk (Наука и техника)
The paper considers taxation problems of production resources in the Republic of Belarus. It has revealed disadvantages of the current taxation system and some recommendations on taxation rates have been proposed with the purpose to stimulate resource saving and innovation introduction at enterprises.